2014
DOI: 10.5933/jkapd.2014.41.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Sedation Practices by Pediatric Dentists

Abstract: The aim of this study was to establish the appropriate guidelines in the sedation techniques and to organize the continuing education programs for the sedation in future under the direction of Committee on Sedation, Education and Research under the Korean Academy of Pediatric Dentistry(KAPD). The surveys on the sedation technique were performed on 111 organizations which practices the sedation and responded to the survey via online and e-mail by February 2014. The collected survey were analyzed. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Midazolam has a very small toxicity rate, anticonvulsant, muscle-relaxant effects, and fewer effects on cardiovascular and respiratory systems [ 24 25 ], and produces anterograde amnesic effects wherein patients do not remember facts such as the surgical procedure, surgical pain, or convertsations during the sustained efficacy period [ 26 27 ]. To date, domestic pediatric dentists have mainly administered midazolam via submucosal, intranasal, and intramuscular routes [ 28 ]. Intravascular sedation has advantages in that it produces a rapid onset of action, offers fast recovery and easy density titration, and enables additional agents to be administered [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam has a very small toxicity rate, anticonvulsant, muscle-relaxant effects, and fewer effects on cardiovascular and respiratory systems [ 24 25 ], and produces anterograde amnesic effects wherein patients do not remember facts such as the surgical procedure, surgical pain, or convertsations during the sustained efficacy period [ 26 27 ]. To date, domestic pediatric dentists have mainly administered midazolam via submucosal, intranasal, and intramuscular routes [ 28 ]. Intravascular sedation has advantages in that it produces a rapid onset of action, offers fast recovery and easy density titration, and enables additional agents to be administered [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dental Society of Anesthesiology also showed that the most preferred route of sedative administration for children was oral, while the most preferred sedative combination was CH, hydroxyzine, and N 2 O inhalation sedation [6,7].…”
Section: Academy Of Pediatric Dentistry (Kapd) and Koreanmentioning
confidence: 99%
“…mucosa and inducing adverse effects such as nausea and vomiting, it is often used in combination with hydroxyzine, which has anti-vomiting and sedative effects[35].According to a survey of KAPD members by Yang et al[6], a higher proportion of participants preferred acombination of two or more drugs and routes of administration including N 2 O inhalation to single-drug treatment, and 67.6% of participants used a combination of sedatives, CH, hydroxyzine, and N 2 O. However, administering two or more sedatives can increase the risk of adverse events [4].…”
mentioning
confidence: 99%
“…The amount, type, and mixtures of drugs used during sedation are related to the side effects [ 8 ]. In a survey of pediatric dentists who used sedation, Yang et al [ 9 ] reported in 2014 that 88% had patients who experienced side effects such as nausea, vomiting, overexcitement, difficulty breathing, oversedation, foreign body aspiration, and drug allergy, among others. Most dental treatments involve procedures during which dentists invade the airway.…”
Section: Introductionmentioning
confidence: 99%